COVID-19 vaccination for children with pulmonary hypertension: efficacy, safety and reasons for opting against vaccination - Zhang, Zeying; Wang, Dan; Zuo, Wanyun; Wang, Xun; Yang, Fan; Luo, Haiyan; Xiao, Zhenghui; Liu, Qiming; Xiao, Yunbin (Frontiers in Pediatrics, 2023)
Objective: To determine the reasons why pulmonary hypertension (PH) children refused vaccination against COVID-19, evaluate the safety and efficacy of COVID-19 vaccine in PH children. Study design: This retrospective cohort study included congenital heart disease-associated pulmonary arterial hypertension (CHD-PAH) and bronchopulmonary dysplasia associated PH (BPD-PH) children who were divided into vaccinated group and non-vaccinated group. Univariate logistic regression analysis and multivariate logistic regression analysis were conducted to explore the reasons why PH children refused COVID-19 vaccine. Then, the prevalence, the number of symptoms, and the severity of COVID-19 disease were compared between the vaccinated and unvaccinated groups. Result: We included 73 children and 61 children (83.6%) were unvaccinated. The main reasons for not being vaccinated were fear of worsening of existing diseases (31%). Age < 36 months (RR: 0.012; P < 0.001) and the presence of comorbidities (RR = 0.06; P = 0.023) were risk factors influencing willingness to vaccinate. The most common adverse events (AEs) were injection site pain (29.6%). COVID-19 vaccines are safe for PH children. The prevalence of COVID-19 disease decreased in PH children after vaccination (RR = 0.51; P = 0.009). 1 month after negative nucleic acid test or negative antigen test, PH children in the vaccinated group had fewer symptoms (P = 0.049). Conclusions: The vaccination rate of COVID-19 vaccine is low in CHD-PAH and BPD-PH children while COVID-19 vaccines are safe. Vaccination can reduce the prevalence of COVID-19 disease and the number of symptoms 1 month after negative nucleic acid or antigen tests.